Intellectual outcome from 1 to 5 years after epilepsy surgery in 81 children and adolescents: A longitudinal study. (October 2021) - Laguitton, Virginie; Desnous, Béatrice; Lépine, Anne; McGonigal, Aileen; Mancini, Julien; Daquin, Géraldine; Girard, Nadine; Scavarda, Didier; Trébuchon, Agnès; Milh, Mathieu; Bartolomei, Fabrice; Villeneuve, Nathalie
Abstract: Objective: This longitudinal study aimed to measure the time course of intellectual changes after pediatric focal resective epilepsy surgery and to identify their predictors. Methods: We analyzed a cohort of 81 school-aged children with focal epilepsy and intractable seizures who underwent neurosurgery (focal resection) from 2000 to 2018 in La Timone Hospital (Marseille). Neuropsychological assessments were carried out before and then 1, 2, 3, and 5 years after epilepsy surgery. Results: Eighty-one patients with a median age at surgery of 13.74 years [4.25] were enrolled. Overall, 45 of the 81 (55%) recruited patients were improved after the surgery on at least one of the five domains of the Wechsler Intelligence Scale. Temporal lobe localization and postoperative seizure freedom were the main prognostic factors impacting intellectual outcome (improvement and decline) after epilepsy surgery. Younger patients at surgery were less likely to have a postoperative IQ decline. Intellectual improvement after epilepsy surgery could be delayed for up to 5 years after surgery and concerned all intellectual domains except the Verbal Comprehension Index (VCI). Intellectual decline after epilepsy surgery occurred mainly during the first two years after the surgery and was reflected in full-scale intelligence quotient (FSIQ) and Working Memory Index (WMI). Conclusions: Our study points out that children and adolescents with TLE who achieved freedom from seizure after epilepsy surgery are the leading candidates for achieving postoperative intellectual improvement. This enhancement in intellectual function shows a long time course, whereas intellectual decline is evidenced earlier. Highlights: More than half of patients tested twice before the surgery experienced intellectual decline. Baseline intellectual functions were not correlated with the postoperative intellectual outcome. Patients with temporal lobe epilepsy achieving freedom for seizures after the surgery were the most likely to achieve intellectual improvement. Intellectual improvement showed a long-time course with delayed occurrence for up to five years after the surgery, whereas intellectual decline was evidenced earlier, during the first two years of follow-up. Intellectual improvement concerned all intellectual domains except Verbal Comprehension Index, whereas the intellectual decline was mainly reflected in the full-scale intelligence quotient and Working Memory Index.